2003
DOI: 10.1081/pfc-120019896
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Atrazine and Ametryne Herbicides in Barbados Sugar Cane Plantation Soils and Water

Abstract: The photodegradation kinetics of atrazine (2-chloro-6-(ethylamino)-4-isopropylamino-1,3,5-triazine) and ametryne (2-methylthio-4-ethylamino-6-isopropylamino-s-triazine), in fresh and coastal salt water from Barbados, were measured under irradiation with artificial solar and UV254-radiation. The first-order rate constants were greater for ametryne than for atrazine, and the rates were reduced in seawater relative to fresh water, and in soil slurries relative to fresh water. However, rates were accelerated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Yang et al [6] found that a commercial activated carbon had an adsorption capacity of 230 mg ametryn adsorbed/g activated carbon at pH 6.07 when aqueous equilibrium concentration of ametryn was around 36 mg/L. McMartin et al [7] investigated ametryn decomposition by several advanced oxidation processes (AOPs). Ametryn degradation was a pseudo-first-order reaction under photoradiation.…”
Section: Introductionmentioning
confidence: 98%
“…Yang et al [6] found that a commercial activated carbon had an adsorption capacity of 230 mg ametryn adsorbed/g activated carbon at pH 6.07 when aqueous equilibrium concentration of ametryn was around 36 mg/L. McMartin et al [7] investigated ametryn decomposition by several advanced oxidation processes (AOPs). Ametryn degradation was a pseudo-first-order reaction under photoradiation.…”
Section: Introductionmentioning
confidence: 98%
“…Faster photolysis was reported in spring water (pH 7.5, 2.3 mg C per L) compared to ocean water, but a direct photolysis control was not included and the organic carbon content of the ocean water was not specied. 333 Studies using model sensitizers provide information about the reactivity of the herbicide with reactive species. Triplet sensitizers accelerate the photodegradation of ametryne, 36,334,335 while the herbicide is relatively unreactive towards singlet oxygen 335,337 and CO 3 À c. 30 Photolysis of iron in acidic solutions results in the photodegradation of ametryne via reaction with cOH.…”
Section: Triazine Herbicidesmentioning
confidence: 99%
“…Triplet sensitizers accelerate the photodegradation of ametryne, 36,334,335 while the herbicide is relatively unreactive towards singlet oxygen 335,337 and CO 3 À c. 30 Photolysis of iron in acidic solutions results in the photodegradation of ametryne via reaction with cOH. 333,336 The photolysis of atraton has only been studied under environmentally relevant conditions using model sensitizers, rather than DOM. The photodegradation of atraton is accelerated in the presence of model triplet sensitizers.…”
Section: Triazine Herbicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…O processo foto-Fenton é reconhecidamente uma alternativa para tratamento de água contaminada por pesticidas em baixas concentrações (SORIANO-MOLINA et al, 2019). Estudos comprovaram a eficiência deste processo na remoção de várias classes de pesticidas incluindo produtos à base de AMT, ATZ, IMD e TBT presentes em água superficial (GARKUSHEVA et al, 2017;MCMARTIN et al, 2003;PULGARIN et al, 2016;SILVA et al, 2010). Portanto, o processo foto-Fenton aplicado de forma isolada ou combinado a outros processos de tratamento pode ser alternativa eficiente e deve ser avaliada para o tratamento de efluentes industriais agroquímicos contendo pesticidas em altas concentrações.…”
Section: Tratamento De Efluente Industrial Agroquímicounclassified